Lean manufacturing production management model to increase the efficiency of the production process of a MSME company in the chemical sector - Mau, Milagros (2019)
In recent decades, the demand for a wide variety of products, lead to the requirement of having a reduced cost of manufacturing, shorter cycle times and perfect quality; forcing companies to implement different engineering techniques to have the best manufacturing system. With which it seeks to efficiently control the process, provide an optimal area of work, establish performance standards with respect to the operations that the company performs, thus generating better results in the organization to achieve higher levels of user satisfaction. In the case of the study, the main line of production in the company was analyzed, detecting that representative costs originated from reprocessing and downtime. The result of greater impact obtained was the reduction of the problems in one (60%) and (15%) respectively. In this way, it is expected that companies in the paint industry or products related to the sector can use the results obtained as a reference in their process of continuous improvement, improving the management and performance of the organization and customer satisfaction.